2021
DOI: 10.3389/fcell.2021.788680
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Osteoclast Biological Behavior

Abstract: With the progress of the aging population, bone-related diseases such as osteoporosis and osteoarthritis have become urgent problems. Recent studies have demonstrated the importance of osteoclasts in bone homeostasis, implying these will be an important mediator in the treatment of bone-related diseases. Up to now, several reviews have been performed on part of osteoclast biological behaviors such as differentiation, function, or apoptosis. However, few reviews have shown the complete osteoclast biology and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 186 publications
(254 reference statements)
1
36
0
3
Order By: Relevance
“…Sphk-mediated SIP/SIPR interaction could activate RANK/RANKL signaling known to commit the joint to chronic inflammation, destruction of cartilage, and bones during the pathogenesis of RA. 117,118 The induction of RANK/RANKL signaling results in the stimulation of TRAF6, which in turn orchestrates the activation of MAPKKs, PI3K, and TBK1 to mediate the activation of several transcription factors, including AP-1 and NF-κB downstream. Dysregulation in signaling along the SIP/Sphk axis, mainly during infectious diseases, has been greatly attributed to the development of RA.…”
Section: Intracellular Signaling As Therapeutic Targets Of Ramentioning
confidence: 99%
“…Sphk-mediated SIP/SIPR interaction could activate RANK/RANKL signaling known to commit the joint to chronic inflammation, destruction of cartilage, and bones during the pathogenesis of RA. 117,118 The induction of RANK/RANKL signaling results in the stimulation of TRAF6, which in turn orchestrates the activation of MAPKKs, PI3K, and TBK1 to mediate the activation of several transcription factors, including AP-1 and NF-κB downstream. Dysregulation in signaling along the SIP/Sphk axis, mainly during infectious diseases, has been greatly attributed to the development of RA.…”
Section: Intracellular Signaling As Therapeutic Targets Of Ramentioning
confidence: 99%
“…OC are mononuclear macrophages that are differentiated from myeloid progenitor cells in the bone marrow and stimulated by various chemokines, transcription factors, cytokines, and other signaling factors to fuse into multinucleated cells and eventually activate into a multinucleated giant cell with bone resorption function [4] . The process of OC differentiation is modulated by a variety of signaling molecules, RANKL is the most critical factor throughout the process [5] . In recent years, more and more studies have suggested that RANKL is an important target for the treatment of bone destruction in RA.…”
Section: Research Backgroundmentioning
confidence: 99%
“…OB plays an important role in the maintenance of bone homeostasis. OB is mainly differentiated from mesenchymal progenitor cells in the stroma of the inner and outer periosteum and bone marrow, and can speci cally secrete a variety of bioactive substances that regulate bone formation and reconstruction processes [9] . The Wnt/β-catenin pathway is one of the important signaling pathways in the differentiation of OB and the regulation of bone formation, bone homeostasis and bone density.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…M-CSF not only stimulates the proliferation and survival of the OC precursor cells but also upregulates RANK expression (Asagiri and Takayanagi, 2007). The RANKL-induced osteoclastogenesis is a sequential process comprising three stages: integration to its receptor RANK to recruit the adaptor molecule TNF receptor-associated factor 6 (TRAF6), resulting in mitogen-activated protein kinases (MAPKs) and nuclear factor-kappa B (NF-κB) activation, and promoting the expression of OCs-typical genes (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%